Dinamika Sosio-Ekonomi dalam Preferensi Taman Kanak-kanak: Analisis Persepsi Masyarakat di Sumatera Utara - Indiyanti, Luluk; Saragi, Suci Nurul Akhwatni; Andriani, Yuyun; Saragih, Nabila Riyani Amanda; Sihombing, Enjelina Vincere (STAI Auliaurrasyidin Tembilahan, 2024)
Early childhood education (PAUD), including Kindergarten (TK), plays an important role in shaping children’s character. In North Sumatra, the many choices of kindergartens make parents’ decisions in choosing influenced by various factors, especially income level. This study aims to explore the level of influence of income on public perception in choosing kindergartens in North Sumatra. This study uses a qualitative approach with a population in 5 sub-districts in North Sumatra. The sample consists of parents who have children aged 4-6 years. Data collection techniques include observation and in-depth interviews with instruments in the form of interview guidelines. Data analysis was carried out using triangulation techniques to ensure the validity of the results. The results of the study indicate that income level plays an important role in shaping parents’ preferences in choosing kindergartens. Parents with higher incomes tend to choose kindergartens with superior facilities and criteria, while those with lower incomes consider location and cost more. Therefore, this study provides insight into the importance of economic factors in educational decisions.